PENERAPAN PSAK 73 PADA PERUSAHAAN PERTAMBANGAN YANG TERDAPAT DI BURSA EFEK INDONESIA PERIODE 2019 - Salfadilla Rahmawati (Jurnalku, 2021)
PSAK 73 is a new accounting standard that adopts the old policy of IFRS 16. PSAK 73 regulates how an asset is recognized, measured, presented and disclosed in the financial statement. Lessees are only allowed to classify lease as finance lease except for short-term lease and lease where the underlying asset is of low value. This study aims to determine the impact of the application of PSAK 73 on lease on the company's financial performance with financial ratios. The sample of this study is two mining sector companies listed on the Indonesia Stock Exchange in 2019. This study uses a qualitative method with data collection techniques. In addition, the model method used is the constructive capitalization of lease developed by Imhoff, Lipe, and Wright (1991). The results of the study indicate that rental capitalization does not have a significant impact on the company's financial statement, with the current ratio and fixed ratio of the two companies decreasing. Net profit margin (NPM), return on assets (ROA), and return on equity (ROE) did not change. Debt to assets (DAR) and debt to equity (DER) have increased.